ABOUT POSSIBILITIES OF USING OF THE NEURAL NETWORKS METHODS FOR COMPUTER-AIDED DESIGN OF CHILL AUXILIARIES - T. V. Matjushinets; L. V. Markov (Литьë и металлургия)
The analysis of the methods of neuron nets, which are used for solving of some problems of foundry, is presented. It is shown that the problems of projection of chill auxiliaries can be solved by means of the methods of neuron nets.